Food environment research in Tanzania: A desk review - Sehgal, Mrignyani; Clarke, Rebecca Namara; Marshall, Quinn; Kumar, Neha (International Food Policy Research Institute, 2024)
Key Findings • Research in Tanzania has focused on cultivated food environments in rural contexts, while urban and peri-urban contexts, and market food environments are understudied; • Seasonality limits affordability and availability of nutritious foods; wild food environments may help maintain diet quality and food security, but access to them is threatened by deforestation and conservation efforts; • Informal food vendors are important sources of fruit and vegetables in urban areas.